Hubungan Gaya Kepemimpinan Transformasional, Gaya Komunikasi, Etos Kerja dan Motivasi Kerja Terhadap Kinerja Guru di SMK Negeri 1 Tejakula - N.S. Rosawidiani; N.L.G.E. Sulindawati; I.G.K.A. Sunu (Pascasarjana Universitas Pendidikan Ganesha, 2022)
This study aims to 1) identify and describe a significant positive relationship between transformational leadership style and teacher performance at SMK Negeri 1 Tejakula, 2) identify and describe a significant positive relationship between principal communication styles and teacher performance at SMK Negeri 1 Tejakula, 3 ) know and describe a significant positive relationship between work ethic and teacher performance at SMK Negeri 1 Tejakula, 4) know and describe a significant positive relationship between work motivation and teacher performance at SMK Negeri 1 Tejakula, 5) know and describe simultaneously whether there is a positive relationship between transformational leadership style, communication style, work ethic and work motivation with teacher performance at SMK Negeri 1 Tejakula. The population in this study were teachers at SMK Negeri 1 Tejakula, Tejakula District, Buleleng Regency, totaling 50 people. The sample used in this study was the Krejci and Morgan formula, the number of samples for a population of 50 was 44. The data collection method used documents and questionnaires. Data analysis techniques were carried out using correlation analysis techniques and regression analysis. The research results show that; (1) the headmaster's transformational leadership style correlated significantly with teacher performance with a correlation of 57.7%, (2) communication style significantly correlated with teacher performance with a contribution of 71.0%, (3) work ethic significantly correlated with teacher performance with a contribution of 75.5%, (4) work motivation correlated significantly with teacher performance with a contribution of 49.7% and (5) principal transformational leadership style, communication style, work ethic, and work motivation together significantly correlated with teacher performance with a correlation of 85.2%.